Análisis Psicocrítico de la Simbología del Purgatorio en la obra “La Divina Comedia” de Dante Alighieri. - Jiménez Jiménez, Michelle Angélica (2022)
The present research results in an analysis focused to the field of literature and psychology. Thus, its purpose is the use of the psycho-critical method in the symbolism of the Purgatory of the Divine Comedy. Also, its importance lies in the originality, since this method has not been used before in a classical work. There are previous inquiries about the subject, however, most have avoided using it in a work of the Renaissance. It was intended to check the effectiveness of the psycho-critical method and so, to build a psycho-biography of the author. The proposed methodology is focused to a documentary design, whose approach is qualitative, descriptive level and its modality is supported by bibliographic research. Its main results are the obtaining of record sheets in which the obtained symbology is evidenced, the use of obsessive metaphors and the presence of the personal myth. This helped to have a better understanding of the work; seen from the author’s biography. In the same way, it contributed in the verification of the method’s effectiveness, so that it can be used in future investigations. Finally, the implication that led to the research was the consideration of bibliographic information to provide guidelines to teachers and students in the elaboration of future analyses in which psycho-criticism is applied. Its transcendence lies in the contribution to the recovery of this method and to the elaboration of a psychobiography about Dante Alighieri, favoring the reader’s vision at the moment of the enjoyment of the work, since literature goes beyond aesthetic enjoyment, it becomes a space of self-knowledge.